Water hyacinth bioremediation for ceramic industry wastewater treatment-application of rhizofiltration system - Siti Hanna Elias; Maketab Mohamed; Aznah Nor-Anuar; Khalida Muda; Mohd Arif Hakimi Mat Hassan; Mohd. Nor Othman; Shreeshivadasan Chelliapan (Universiti Kebangsaan Malaysia, 2014)
In the present study, capability of water hyacinth in removing heavy metals such as Cadmium (Cd), Chromium (Cr), Copper (Cu), Zinc (Zn), Iron (Fe), and Boron (B) in ceramic wastewater was investigated. The metal removal efficiency was identified by evaluating the translocation of metals in roots, leaves and shoot of water hyacinth. The heavy metal removal efficiency followed the order Fe>Zn>Cd>Cu>Cr>B during the treatment process. Water hyacinth had luxury consumption of those 6 elements. This study used the circulation system with 3 columns of plants which functioned as bioremediation of the sample. The concentration of metals in roots is much higher 10 times than leaves and stems. Roots give the result of metalR>metalL. The removal concentration from water hyacinth was estimated under pH of 8.21 to 8.49. This study proves water hyacinth to be a best plant for phytoremediation process.